Analisis Titik Ekuilibrium Model Epidemi Sir dengan Efek Demografi - Nurul Hikmah (Beta: Jurnal Tadris Matematika, 2011)
In this paper, we consider a SIR epidemic model with demographic effects. By carrying out a global analysis of the model and studying the locally stability of the equilibrium in this paper, and make some predictions implied by this model about some qualitative aspects of the spread of a disease, we show that the equilibrium of a SIR epidemic model is locally astatically stable.